2017
DOI: 10.1038/s41598-017-06031-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of A Novel Prox1-EGFP Lymphatic and Schlemm’s Canal Reporter Rat

Abstract: The lymphatic system plays a key role in tissue fluid homeostasis, immune cell trafficking, and fat absorption. We previously reported a bacterial artificial chromosome (BAC)-based lymphatic reporter mouse, where EGFP is expressed under the regulation of the Prox1 promoter. This reporter line has been widely used to conveniently visualize lymphatic vessels and other Prox1-expressing tissues such as Schlemm’s canal. However, mice have a number of experimental limitations due to small body size. By comparison, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
3
46
0
Order By: Relevance
“…Thus, the identity, character, and function of this enigmatic lymphatic sac need further investigation. We also confirmed this pattern of nasal-side predilection of the ocular lymphatic development using a different species, Prox1-EGFP lymphatic reporter rats (37). Indeed, we observed a comparable pattern of ocular lymphangiogenesis in rats: the limbal and conjunctival lymphatics in newborn rat pups (P2) migrated from the nasal side and bifurcated to encircle the cornea (Fig.3L).…”
Section: In Vivo Detection Of the Ocular Lymphatic Vessel Connection supporting
confidence: 80%
See 3 more Smart Citations
“…Thus, the identity, character, and function of this enigmatic lymphatic sac need further investigation. We also confirmed this pattern of nasal-side predilection of the ocular lymphatic development using a different species, Prox1-EGFP lymphatic reporter rats (37). Indeed, we observed a comparable pattern of ocular lymphangiogenesis in rats: the limbal and conjunctival lymphatics in newborn rat pups (P2) migrated from the nasal side and bifurcated to encircle the cornea (Fig.3L).…”
Section: In Vivo Detection Of the Ocular Lymphatic Vessel Connection supporting
confidence: 80%
“…As we and others have previously documented (3-6, 37), both the ocular lymphatics and Schlemm's canal were readily detectable in the Prox1 promoter-driven reporter mice by their EGFP expression ( Fig It has not been reported whether the limbal lymphatics harbor the luminal valves, a hallmark of collecting lymphatics, and how they extend beyond the limbus area. Toward these questions, we next performed further studies on the limbal lymphatics using two different rodent species, Prox1-tdTomato mice (36) and Prox1-EGFP transgenic rat (37). Indeed, we found that the limbal lymphatics are directly connected to the conjunctival lymphatics through multiple short lymphatics present along the corneal edge ( Fig.1Q-U).…”
Section: Visualization Of the Ocular Surface Lymphatic Vessels And Scmentioning
confidence: 95%
See 2 more Smart Citations
“…These new mouse models provide opportunities for future research not only in mice but also in other animal models based on genomic conservation between species (e.g., genomic sequences used to create transgenic Prox1-EGFP mice are highly conserved in other species)[73]. For example, Jung et al developed a transgenic rat model for studying surgical physiology along with convenient structural and functional analysis of lymphatic vessels expressing Prox1[43]. …”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%